Omnimetrics and Awards - Bruno S. Frey (Center for Economic Studies and ifo Institute (CESifo), 2017)
The digital revolution has led to a quantification of ever more areas of human life and society. At the same time, there is an explosion of the number of awards, which by their very nature are based on non-quantified performance. Will quantification take over completely, leading to "omnimetrics"? The paper argues that this will not be the case. An economic explanation for the paradoxical existence of two totally different developments is offered: The value of awards is the higher, the stronger is the effort to quantify. The two developments depend on each other. The more digitalized the world is, the more non-quantified and non-quantifiable aspects of life are cherished. The quantification mania not only raises the value of awards but also the importance of personal relationships, of friendship, love and admiration. While digitalization will proceed and will determine increasingly larger parts of our lives, it is hypothesized that the non-quantified aspects of life will not disappear but flourish.
Keywords: A13; C80; D46; D80; Z10; 330; awards; digital world; quantification; rankings; ratings; intrinsic motivation